A Modified Method for Rapid Genomic DNA Extraction from Tuberose - Ali, Qasim; Bala Salisu, Ibrahim; Muhammad Akhtar Khan, Saleem; Ahmad, Naveed; Ali Shahid, Ahmad (BioScientific Review, 2019)
The isolation of high yield and quality genomic DNA is crucial for studying the molecular genetics of plants. However, high contents of secondary metabolites, especially in medicinal and aromatic plants, interfere with the extraction of clean DNA, thereby rendering it useless for downstream analyses such as DNA amplification, restriction, sequencing and cloning. The chemotypic heterogeneity among plant species may not permit high quality DNA isolation with a single protocol, thus a species-specific extraction method is required for quality extractions. Here, we present a modified cetyltrimethylammonium bromide (CTAB) protocol for good quality DNA extraction from tuberose, which is an important plant for perfume and pharmaceutical industry due to its pleasant fragrance and essential oil content. In contrast to other CTAB methods, the modified procedure is rapid, omits the use of liquid nitrogen and phenol, uses inexpensive and less hazardous reagents, and requires only ordinary laboratory equipment. The procedure employed the high concentration of NaCl and use of PVP-10 to get rid of problems associated with polysaccharides and polyphenols, respectively. The yield and quality of extracted DNA were fairly good and amenable for downstream analyses. Moreover, to our knowledge, the described method is the first report of a modified DNA extraction protocol for tuberose.